Engineering of Health Organization and Life Insurance Costs on Customer Loyalty by Creating Customer Value - Kafshdar Goharia, Mahdad; Karimi, Mohammad (International Journal of Engineering and Technology, 2018)
At the current competitive world and the turbulent market caused by presence of different brands in each industry, customer is axis of business in every industry and customer loyalty to organization can be the main factor in gaining position in the market and competitive advantage. Hence, the main objective of this study is to analyze the effect of service quality and life insurance costs on customer loyalty by creating customer value. In terms of purpose, this study is an applied research and in terms of data collection method, it is descriptive study in kind of analytical-survey research. The data used in this study was collected from customers of Iran Life Insurance in Mashhad using simple sampling and using questionnaire derived from study of [1] and its validity and reliability has been confirmed. Finally, 202 questionnaires were analyzed using PLS software, which is in kind of structural equations. The results obtained from this study confirmed all hypotheses and showed direct impact ofservice quality and service cost on customer value, value and service quality on customer loyalty and the reverse impact between service costs and loyalty has been also indicated.Â Â